"That Looks Hard!": Effects of Objective and Perceived Textual Complexity on Factual and Structural Political Knowledge. (2nd October 2019) - Tolochko, Petro; Song, Hyunjin; Boomgaarden, Hajo
Abstract : Communication of political information is vital for a well-functioning democratic system, and texts are one of the main mediums of politics. Most studies dealing with political text consider how such texts communicate content, rather than the structural characteristics of texts themselves. The current study focuses on complexity as one of the focal structural characteristics of political text. Previous research showed that different types of textual complexity affect learning processes. Such prior studies are, however, limited both conceptually and empirically. This study addresses these gaps by employing a large-scale experimental design ( N = 822), investigating how different dimensions of textual complexity affect factual and structural political knowledge, and whether such relationships are mediated through perceived complexity. Results indicate that different levels (high vs. low) and different dimensions of textual complexity (semantic vs. syntactic) influence reader's perception of text, as well as their factual and structural knowledge. Only semantic complexity has an effect on one's perceived complexity, which in turn negatively affects factual and structural knowledge. Syntactic complexity directly lowered one's factual knowledge acquisition, while there was no direct effect of syntactic complexity on structural knowledge. The results suggest that text complexity indeed plays an important role in political information acquisition, and our findings also highlight the importance of perception in mediating the structural effects of the text.